"A Bright Continuous Flow": Phantasmagoria and History in A Tale of Two Cities. Issue 4 (2020) - Shubert, Amanda
Abstract : This essay explores how Charles Dickens's representation of history in A Tale of Two Cities (1859), his historical novel of the French Revolution, is influenced by the Phantasmagoria. The Phantasmagoria was an optical ghost show popularized in Paris in the 1790s by the showman Etienne Gaspard Robertson. Using a hidden magic lantern in a pitch-dark room, Robertson projected images of ghosts and skeletons as well as historical personages from the French Revolution. Drawing on Dickens's own writings on the Phantasmagoria, the essay argues that Dickens's approach to historical fiction is informed by the Phantasmagoria's medium-specific effects and its cultural association with history and historical memory. Specifically, Dickens's turn to a dialectic of continuity and discontinuity to represent historical temporality is influenced by the dialectical visual effects of the Phantasmagoria and related mid-nineteenth-century optical technologies. A Tale of Two Cities has always resisted the dialectical-materialist paradigm for the nineteenth-century historical novel first developed by Georg Lukács and more recently elaborated by Fredric Jameson. By employing a media archaeological framework, this essay offers a revitalized approach to Dickens's historical representation that contextualizes it within nineteenth-century theories and discourses of optical perception.